Manajemen Strategik UP/J SMKN 3 Mataram - M. Ary Irawan; Adisel Adisel (Journal Of Administration and Educational Management (ALIGNMENT), 2018)
The objective of the study was to find out the strategical management UP/J SMKN 3 Mataram. It was a qualitative study with case study method. The techniques to collect the data were observation, interview, and documentation. The findings were (1) strategical planning, including: (a) compatibility of UP/J program goal with school vision and mission and (b) the arrangement of UP/J program periodically; (2) strategical application, including: (a) cooperation with government institutions and private institutions, (b) marketing of UP/J carried out by school society including school principal, teachers, students, parents and alumni, (c) empowering alumni and students as employees, (d) executing production schedule out of reaching and learning activities, and , (e) transparency in financial management ; and (3) strategical supervising, including: (a) the distribution of customers satisfaction instruments, (b) the supervising in form of the report periodically each semester and each year. In conclusion, the strategical management of UP/J SMKN 3 Mataram includes; planning, excecuting, and supervising. Keywords: Strategical Management, Production Unit, School Service